Combination of intraoperative indocyanine green video-angiography FLOW 800 and computed tomography perfusion to assess the risk of cerebral hyperperfusion syndrome in chronic internal carotid artery occlusion patients after revascularization surgery - Du, Juan; Shen, Jun; Li, Jian; Zhang, Fayong; Mao, Renling; Xu, Yinghua; Duan, Yu (Frontiers in neurology, 2023)
To study the changes of corticocerebral hemodynamics in surgical area and postoperative hyperperfusion syndrome in patients with chronic internal carotid artery occlusion (CICAO) by intraoperative indocyanine green videoangiography (ICGA)-FLOW 800 and CT perfusion after superficial temporal artery (STA)-middle cerebral artery (MCA) bypass surgery. From October 2019 to January 2021, 77 patients diagnosed with CICAO underwent direct bypass surgery at Huadong hospital (affiliated with Fudan University) were enrolled. Regions of interest (ROIs) at STA, proximal MCA (PMCA), distal MCA (DMCA), cortical blood capillary (CBC), and cortical vein (CV) were identified after anastomosis by ICGV-FLOW 800 including peak fluorescence intensity (PFI), time to peak (TTP), and area under the time curve (AUC) of fluorescence intensity. All patients underwent perfusion-weighted CT before bypass surgery and those patients with HPS were verified by CTP after bypass. 14 patients with HPS were verified by perfusion-weighted CT after bypass. In HPS group, the AUC of DMCA was significantly larger (T = -3.301, = 0.004) and TTP of CBC was shorter (T = -2.929, = 0.005) than patients in non-HPS group. The larger AUC of DMCA (OR = 3.024, 95%CI 1.390-6.578, = 0.0050) was an independent risk factor by further multivariate logistic regression analysis. The hemodynamic changes of cortical vessels during STA-MCA bypass surgery could be recorded accurately by ICGV-FLOW 800. Furthermore, the increased AUC of DMCA and shorter TTP of CBC may be potential risk factors of HPS.